2011
DOI: 10.1089/jamp.2010.0849
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Lung Delivery of Nasally Administered Aerosols During Noninvasive Ventilation—An Application of Enhanced Condensational Growth (ECG)

Abstract: Background: Aerosol drug delivery during noninvasive ventilation (NIV) is known to be inefficient due to high depositional losses. To improve drug delivery efficiency, the concept of enhanced condensational growth (ECG) was recently proposed in which a submicrometer or nanoaerosol reduces extrathoracic deposition and subsequent droplet size increase promotes lung retention. The objective of this study was to provide proof-of-concept that the ECG approach could improve lung delivery of nasally administered aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 60 publications
0
71
0
Order By: Relevance
“…Longest and colleagues [33][34][35][36][37][38][39][40][41][42][43][44][45][46] have been exploring approaches to generate submicron particles, which are less likely to impact in the circuit, but grow large enough in the respiratory tract that they are likely to be deposited in the lungs. This work is preclinical, but has potential for benefit if adapted to clinical use.…”
Section: Approaches To Improve Aerosol Delivery During Hfncmentioning
confidence: 99%
“…Longest and colleagues [33][34][35][36][37][38][39][40][41][42][43][44][45][46] have been exploring approaches to generate submicron particles, which are less likely to impact in the circuit, but grow large enough in the respiratory tract that they are likely to be deposited in the lungs. This work is preclinical, but has potential for benefit if adapted to clinical use.…”
Section: Approaches To Improve Aerosol Delivery During Hfncmentioning
confidence: 99%
“…For both of these studies, delivery rates to the lung are expected to be significantly lower than the fraction exiting the cannula interface due to deposition in the nasal airways. (13)(14)(15) Depositional losses in nasal cannulas at higher flow rates consistent with NPPV and HFT for adults and for different particle sizes have previously not been reported. The administration of pharmaceutical aerosols during other forms of NIV was previously reviewed (8)(9)(10)16) and indicated typical patient delivery rates of less than 1-10% from in vitro studies and 1-6% under in vivo conditions.…”
mentioning
confidence: 94%
“…Condensational growth then occurs when the aerosol and humidity streams combine in the nasopharynx and continue downstream. In the study of Longest et al, (15) both in vitro results and CFD predictions indicated that, with ECG delivery, depositional losses in the NMT region were approximately 15% at a total flow rate of 30 L/min through the model, and condensational growth increased the initially submicrometer aerosol size to approximately 2 lm in the trachea. In comparison, deposition of a conventional 4.7-lm aerosol in the NMT geometry was found to be approximately 70% under identical flow conditions.…”
mentioning
confidence: 97%
See 2 more Smart Citations